Internship Reports and Monograph titled "Comet Assay for Nanotoxicology Assessment - Nanoparticles Genotoxicity Testing" - Cardoso, Sara Patricia Pereira (2019)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia